Indigenous fungi from corn as a potential plant growth promoter and its role in Fusarium verticillioides suppression on corn. Issue 9 (September 2021) - Mirsam, Hishar; Kalqutny, Septian Hary; Suriani,; Aqil, Muhammad; Azrai, Muhammad; Pakki, Syahrir; Muis, Amran; Djaenuddin, Nurasiah; Rauf, Abdul Wahid; Muslimin,
Abstract: Indigenous fungi can suppress infection by pathogens and produce secondary metabolites that directly or indirectly affect plant growth. This study aimed to test indigenous fungi collected from corn plants as biological control agents and their effects on the viability and vigor of corn seeds. Purposive sampling method was used for sampling where soil samples taken from the rhizosphere zone, corn stem and leaf tissue from three locations namely Maros-South Sulawesi, Bone-South Sulawesi, Sigi-Central Sulawesi, Indonesia. Rhizospheric fungi were isolated from soil collected at the rhizosphere and rhizoplane using a serial dilution technique, while the endophytic fungi isolated from the leaves and stem tissues using surface sterilization method. The isolated fungi were cultured on a potato dextrose agar (PDA) medium. An antagonism test was performed using the dual culture method on PDA media with F. verticillioides as target pathogen. Pathogenicity test and the effect of fungi on corn seed germination was carried out using the blotter test method. Parameters observed were; necrotic symptoms on seedlings, growth potential, germination, growth rate, growth simultaneity, vigor index, germination rate, and time needed for 50% of the total germination. The effect of the isolated indigenous fungi on corn growth was carried out in-planta using seedling trays. The results of the blotter test and in-planta test were further confirmed by a physiological characteristic test. And assessing the fungi's ability to dissolve potassium, phosphate, and produce protease enzymes. A total of 89 fungal isolates were isolated and collected from various parts of the corn plant. Nineteen of the 89 fungal isolates showed inhibitory activity against F. verticillioides by ≥ 50% inhibition. The fungal isolates JRP 5 MRS, JRP 9 MRS, JRP 10 MRS, JRP 7 MRS, and JEDF 1B BN were selected based on the tests and showed a consistently positive effect on seed viability and vigor with a value of ≥90%. The isolates did not cause necrosis in corn, and had the ability to suppress the growth of pathogenic F. verticillioides by ≥ 50%. Abstract : Endophytic fungi, Rhizospheric fungi, Plant growth-promoting fungi